2021
DOI: 10.1039/d1tb00783a
|View full text |Cite
|
Sign up to set email alerts
|

Shape anisotropic magnetic thrombolytic actuators: synthesis and systematic behavior study

Abstract: Thrombosis-related diseases are undoubtedly the deadliest disorders. Numerous attempts were made during the last decades to reduce the overall death rate and severe complications caused by treatment delays. Significant progress...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…However, the final result of dissolution was about 10% lower than scuPA alone (Figure d). Such an effect, inhibition of scuPA action by NPs, was previously reported . We suggested that this phenomenon relates to the unspecific adsorption of scuPA on the surface of MNPs and its partial inhibition.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…However, the final result of dissolution was about 10% lower than scuPA alone (Figure d). Such an effect, inhibition of scuPA action by NPs, was previously reported . We suggested that this phenomenon relates to the unspecific adsorption of scuPA on the surface of MNPs and its partial inhibition.…”
supporting
confidence: 66%
“…Such an effect, inhibition of scuPA action by NPs, was previously reported. 43 We suggested this phenomenon relates to the unspecific adsorption of scuPA on the surface of MNPs and its partial inhibition.…”
mentioning
confidence: 98%
“…Magnetic Responsive Nanosystems. Targeted drug delivery by magnetic up-conversion NPs has shown great potential 57,58 and are generated through the encapsulation of rtPA in magnetic porous materials or coating of a surface with magnetic NPs. 59 Fe 3 O 4 has been widely applied due to its high degree of biodegradability and biosafety.…”
Section: Ultrasound Responsivementioning
confidence: 99%
“…The suspendable examples of the mechanical force-based elimination of biofilms and biopolymers mainly involve the application of magnetically active materials, which show superior efficiency under the action of an alternating magnetic field. 23–26…”
Section: Introductionmentioning
confidence: 99%
“…The suspendable examples of the mechanical force-based elimination of biofilms and biopolymers mainly involve the application of magnetically active materials, which show superior efficiency under the action of an alternating magnetic field. [23][24][25][26] Bearing in mind in vivo applications, the material choice should focus on colloidal forms of nanomaterials, without significant intrinsic toxicity caused by, for instance, the spontaneous release of toxic ions or the generation of toxic metabolic products. For this purpose, an FDA-approved antacid based on CaCO 3 27 is an ideal candidate for the development of antibiotic-free abrasive toothpaste due to its inert chemical behavior, its high biocompatibility, the ease of the production of materials with desired shapes and sizes, the drug loading effectiveness, and the potential for surface modification with polymers, surfactants, and other compounds.…”
Section: Introductionmentioning
confidence: 99%